THE CHARACTERISTIC DESCRIPTION OF COMPLIANCE WITH FLUID LIMITATION, INTERDYALITIC WEIGHT GAIN (IDWG), AND QUALITY OF LIFE IN HEMODIALYSIS PATIENTS IN PALEMBANG CITY - Fermata - Sari; Raveinal Raveinal; Esi Apriyanti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Patients with hemodialysis are required to carry out routine care, diet arrangements, and fluid restrictions. The highest non-compliance in patients is fluid restriction. Excessive fluid intake can be seen from weight gain between dialysis time (IDWG). IDWG in hemodialysis patients should not be more than 3.5%, where an increase in IDWG can cause the risk of death and decreased quality of life. However, at the hospital itself, routine identification of fluid restriction non-compliance activities was not carried out, so that there were still many patients with hemodialysis who experienced an increase in IDWG in the moderate and severe categories. The purpose of this study is to explore the characteristics, fluid restriction compliance, IDWG, and quality of life in hemodialysis patients. This is done to plan the provision of further intervention in patients. The design in this study was cross-sectional with sampling techniques with simple random sampling. The results of the study characteristics of respondents at the age of 46-55 years (64.7%) more male sex (55.9%), and high school education (47.1%), all respondents were married (100%), most not working (58.8%), the average length of hemodialysis is 18 months. The mean mean liquid restriction compliance was 27.35, the mean value of IDWG was 4.97 and the mean value of quality of life was 51.72.